Selective cleavage of thioether linkage in proteins modified with 4-hydroxynonenal. - Uchida, K (1992)
The peroxidation of polyunsaturated fatty acids leads to numerous products, including 4-hydroxynonenal (HNE). That 4-hydroxy-2-alkenal compounds react with sulfhydryl groups of proteins to form thioether adducts possessing a carbonyl function has been established [Schauenstein, E. & Esterbauer, H. (1979) Ciba Found. Symp. 67, 225-244]. Taking advantage of the fact that Raney nickel catalyzes cleavage of thioether bonds, we have developed a procedure to quantitate the amount of HNE moiety bound to protein by means of a thioether linkage. Adducts of HNE with N-acetylcysteine and glutathione were prepared, labeled with NaB[3H]H4, and then treated with Raney nickel. The 3H-labeled product was recovered in 85-90% yield from both HNE-N-acetylcysteine and HNE-glutathione adducts in a solvent [10% (vol/vol) methanol/chloroform]-estractable form. Treatment of proteins with HNE led to the disappearance of protein sulfhydryl groups. However, less than 10% of the labeled adducts obtained after subsequent reduction with NaB[3H]H4 could be released in a solvent-extractable form upon treatment with Raney nickel. This and the observation that HNE reacts with proteins lacking a sulfhydryl group attests to the fact that HNE can react with amino acid residues other than cysteinyl residues.